Effect of maternal depression on infant-directed speech to prelinguistic infants: Implications for language development. - Christa Lam-Cassettari; Jane Kohlhoff (PLoS ONE, 2020)
The nature and timing of caregivers' speech provides an important foundation for infant attention and language development in the first year of life. Infant-directed speech is a key component of responsive parent-infant communication that is typically characterised by exaggerated intonation and positive affect. This study examines the effect of postnatal depression on the expression of positive vocal affect and pitch, the quantity of mothers' infant-directed speech input and the timing of vocal responses between mother and infant. Postnatal mothers currently experiencing symptoms of depression (n = 13) were matched to postnatal mothers who were not experiencing symptoms of depression (n = 13), and audio-recorded while playing with their 6-month-old infants. Compared with depressed mothers, non-depressed mothers used a higher mean pitch and pitch range, spoke more, gave faster verbal responses and were rated as expressing more positive valence in their voice. These preliminary findings indicate that mothers experiencing low mood use less infant-directed speech and less exaggerated pitch with prelinguistic infants. Postnatal depression is a major health issue that adversely impacts the parent and child. Early interventions for PND may benefit from identifying ways to support the timing of conversations and mothers' use of appropriate vocal pitch and infant-directed speech modifications. Further research is needed to confirm whether these strategies support early conversations.